Analisis terhadap Tugas dan Peran Juru Sita Setelah Berlakunya Sistem E-Court di Pengadilan Negeri Sragen Kelas 1A - Zellin Eva Handayani; Wahyu Adi Mudiparwanto (CV Rewang Rencang, 2025)
The e-Court system changes the duties and roles of court bailiffs, if previously the work system was carried out conventionally, it is now carried out in a modern manner. This research is conducted to determine and analyse the legal implications of the duties of bailiffs after the implementation of e-Court, as well as to examine the validity of summons made by bailiffs. This research uses normative juridical and empirical juridical methods with statute approach, comparative approach and socio legal research. Although it has a good impact on the duties of bailiffs, it is undeniable that there are challenges and obstacles that need to be evaluated in its application.